Tourism Business, Place Identity, Sustainable Development, and Urban Resilience: A Focus on the Sociocultural Dimension. (January 2021) - Jiménez-Medina, Pilar; Artal-Tur, Andrés; Sánchez-Casado, Noelia
La Unión is a city located in the southeast of Spain with a long mining tradition. Along the twentieth century, this place faced a severe industrial crisis. Building on its history, heritage, and resources, the local economy changed towards the mining heritage tourism business. This article describes such a process of sustainable development and urban resilience through a two-stage approach. First, the focus is on explaining how the locality moved from being a mining industrial area to a mining heritage tourism place. In doing so, the study highlights the key role played by the cooperation of the local government and the nearby university. The second stage shows how the new economic model is firmly rooted on the mining identity of the place and what provides higher levels of sustainability to the destination from a social and cultural view. In this context, the article shows how the place identity model of tourism would be eager to limit the negative impacts usually associated with the spread of tourism, consequently receiving further support by the local population. To better understand the second-stage process, the study defines a theoretical framework and tests it empirically through a structural equation modeling approach. Results of the research provide regional policy advices.